Potentialities of immunological tests in the diagnosis of latent tuberculosis infection and tuberculosis - L. V. Slogotskaya; M. V. Sinitsyn; D. A. Kudlay (Туберкулез и болезни лёгких)
The article assesses existing immunological tests aimed to detect tuberculosis infection (tuberculin skin test, IGRA, skin test with a recombinant tuberculosis allergen). The latest inventions in the development of immunological tests that can differentiate latent tuberculosis infection and active tuberculosis have been analyzed. The difficulties encountered when developing such a test and conducting clinical trials have been demonstrated. The article presents the experience of the Moscow TB service in using the skin test with recombinant tuberculosis allergen as a screening method for tuberculosis infection, its ability to detect the infection at the stage of its development when preventive therapy is most effective since anti-tuberculosis drugs kill mycobacteria that are replicating but not dormant. Such tactics contributed to the incidence rate decrease both in high-risk groups and among the general population.